Can genistein be a potential agent against skin side effects associated with the treatment of breast cancer? - Pawlicka, Magda; Filip, Agata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Despite significant medical advances, cancer treatment is still associated with a high risk of side effects. The treatment is usually invasive and devastating and it affects the overall immunity of the whole organism, including the condition of the skin. In recent years there has been a growing interest in isoflavonoids, due to their wide range of biological and pharmacological activity, especially estrogen-like. It gives a broad perspective of their use as active ingredients of preparations, which eliminate skin lesions associated with oncological treatment. This article is an overview describing preclinical and clinical observations on the basis of available literature. It discusses the influence of genistein on skin health in women after breast cancer treatment. The overview focuses on studies conducted with genistein in vitro or in vivo to demonstrate its effect on skin, and anticancer properties. We selected articles from the last 20 years, available in the PubMed and Google Scholar databases.